The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1123/jsep.2013-0232
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Integrative Model of Doping Use: An Empirical Study With Adolescent Athletes

Abstract: The present study assessed adolescent athletes' intentions toward doping by using an integrative theoretical model. Overall, 650 adolescent athletes from team and individual sports completed an anonymous structured questionnaire including demographic information, social desirability, achievement goals, motivational regulations, sportspersonship orientations, social cognitive variables, and anticipated regret. Hierarchical regression analysis showed that the integrative model predicted 57.2% of the variance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
85
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(103 citation statements)
references
References 43 publications
8
85
1
1
Order By: Relevance
“…The results from Barkoukis et al [6] and Lazuras et al [5] nevertheless suggested that motivational regulations did not inform the process leading to the formation of doping intentions when tested alongside other distal predictors such as achievement goals. These discrepant results can be explained by the use of different scales.…”
Section: Self-determination Theory Self-regulatory Mechanisms and Domentioning
confidence: 96%
See 4 more Smart Citations
“…The results from Barkoukis et al [6] and Lazuras et al [5] nevertheless suggested that motivational regulations did not inform the process leading to the formation of doping intentions when tested alongside other distal predictors such as achievement goals. These discrepant results can be explained by the use of different scales.…”
Section: Self-determination Theory Self-regulatory Mechanisms and Domentioning
confidence: 96%
“…These discrepant results can be explained by the use of different scales. For example, Hodge et al [13] and Chan et al used the Behavioral Regulation in Exercise Questionnaire [29][30][31][32], whereas Barkoukis et al [6] and Lazuras et al [5] used the Sport Motivation Scale [29].…”
Section: Self-determination Theory Self-regulatory Mechanisms and Domentioning
confidence: 99%
See 3 more Smart Citations